(untitled) (Revista Ciência Agronômica, 2018)
The construction of hydroelectric power plants (HPP) may result in environmental problems, such as extensive areas of exposed subsoil and conditions of extreme degradation. These areas require alternative that minimize impact and allow partial recovery of their ecosystem functions and vegetation. This study aimed to evaluate the effects of residue addition (organic/macrophytes - OR and inorganic/ash - AR), hydrogel, and inoculation of microorganisms in degraded soil, cultivated with Jatropha curcas, through fertility and microbial activity. A conserved Cerrado (“savannah”) soil was the source of microorganisms - mainly mycorrhizal fungi. The experiment was conducted for 12 months (during 2010/2011) at the farm of UNESP-School of Engineering/Campus of Ilha Solteira, Selvíria-MS, Brazil, installed in an area where the soil was degraded during the HPP construction, in the 1960s. The experimental design was complete randomized blocks, using a 2×2×4 factorial scheme, i.e., two inoculation treatments (with and without), two hydrogel treatments (with and without), and four residue treatments to introduce the J. curcas (OR, AR, OR + AR, and control without residues), with four replicates and five plants evaluated per replicate. The soil fertility analyses, quantification of microbial biomass carbon (MBC), and released C as CO2 (CO2 -C), microbial quotient (qMic), and metabolic quotient (qCO2 ) were carried out 12 months after planting. The fertility positively responded to the addition of OR and OR + AR, with an increase in pH and SB and reduction in Al and H + Al. The inoculation of soil microorganisms associated with OR and OR + AR residue treatments raised the released CO2 -C, MBC, and qMic. The addition of hydrogel combined with OR treatment contributed to the increase in the values of MBC and qMic.